Is the T-shaped acetabular fracture really likes a "T"? A study based on three-dimensional fracture mapping. Issue 11 (November 2022) - Ye, Pengyu; Guo, Junfei; Tian, Siyu; Wang, Zhongzheng; Li, Junran; Zhao, Ruikai; Hou, Zhiyong; Zhang, Yingze
Abstract: Objectives: To explore the morphological pattern of T-shaped acetabular fractures (T-SAFs) by mapping the fracture line using 3D software. Material and methods: We retrospectively reviewed 1298 consecutive patients with acetabular fractures, and a total of 56 T-SAF patients were enrolled. After the simulated reduction of each fracture in the software, the fracture lines of all patients were overlaid and plotted on a template. A frequency heat map was generated according to the differences in fracture line density distribution. According to the location of fracture lines, all cases were divided into three groups: posterior group, anterior group, extra-posterior group. In surgically treated patients, the surgical approach, fixation methods, and reduction quality were recorded or evaluated. Results: The transverse fracture line was sinuous without involving the acetabular roof, and the longitudinal fracture line sloped forward or backward along the edge of the acetabular fossa to split the obturator foramen. The anterior and posterior edges of the acetabular fossa, the transition zone of the acetabular roof and anterior wall, the transition zone of the superior pubic ramus and anterior wall, and the posterior wall near the greater sciatic notch were areas with high rates of fracture incidence. The posterior group included 26 patients (46.4%) and the distribution of fracture lines resembled a "T" or "Y". The anterior group included 25 patients (44.6%) and the distribution of fracture lines resembled a "7″. The extra-posterior group included 5 patients (8.9%) and the fracture lines run through the ischial body. The surgical strategies vary among different groups of T-SAF patients. Conclusion: Our findings shed light on the characteristics of fracture lines for T-SAFs and provide a reference for surgical treatment strategies.